Detail work of the East door of Sun Temple, Konark - Temples of India Project Team (Jio Institute, 2024)
Detailed work of the East door to Jagamohan, Sun Temple, Konark, Orissa, India. Ganga period, reign of Narasimhadeva I, 1238-58 CE. Image courtesy: Prof. Chedha Tingsanchali.